Metod vizualizacii na osnove multimedijnych sredstv v obucenii techniko-takticeskim dejstvijam junych borcov - Agatovich, I. R. (Scientific Impulse, 2023)
Training process of young wrestlers of the Greek-Roman style has to rely on wide use of multimedia technologies, computer modeling, interactive methods which use staticizes on a new round of scientific judgment a problem of visual teaching methods in modern system of training and training. Use of multimedia means admits necessary and demanded training process of young athletes and though they completely can't and shouldn't replace the trainer, at the same time their use in training allows to present elements of the mastered equipment in more detail, to see own errors of execution on the screen, to correlate the equipment to equipment of reference group. The purpose of the conducted research -justification of opportunity and efficiency of use of multimedia means for visualization of actions of young wrestlers of the Greek-Roman style in the course of performance of tasks on technical and tactical preparation by means of the developed author's program and methodical multimedia complex "Wrestling multimedia".